ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP NASABAH INDUSTRI PERBANKAN DI TENGAH PANDEMI COVID-19 (Studi di Bank Mandiri Jakarta) - Haryono Haryono; Henni Rahayu Handayani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) SARS-CoV-2 is coronavirus a new type ofthat has never been previously identified in humans. to be studied from the perspective of the banking industry customers is the legal protection of banking industry customers in the midst of the Covid-19 pandemic. The approach method in this research is descriptive qualitative analysis, the results in this study are legal protection for independent banking industry customers in the midst of the Covid-19 pandemic in carrying out regulatory and supervisory tasks in the banking sector, regulation and supervision of bank health, including liquidity, profitability , solvency, asset quality, minimum capital adequacy ratio, maximum credit limit, guarantee ratio to deposits and bank reserves, bank reports related to bank health and performance and debtor information system. Then the Impact and Risks of Independent Banking Industry Customers in the Middle of the Covid-19 Pandemic, Impacting the survival of credit customers (debtors) and the banking system itself, Banks will experience difficulties or risk of banking liquidity during the pandemic, especially small banks, Will have an impact on banking income, The provision of services to customers is less than optimal during the pandemic, Customers reduce visits or come directly to bank branch offices and Decreased Asset Quality due to weak economic conditions.